PENGARUH PROMOSI KOPING TERHADAP PENINGKATAN KOPING DALAM MENCEGAH STRES PADA MASYARAKAT - Yeni Devita; Eka Malfasari; Rina Herniyanti; Ihwayuni uni (Universitas Prima Indonesia, 2021)
Coronavirus (COVID-19) is a virus that infects the respiratory system. The Corona pandemic affects the Indonesian economy from trading, investment, and tourism. It gives a big impact on low economic society. A society that is not able to adapt to the effect will be vulnerable to stress. The role of the medic is important to socialize coping to prevent stress on society. This research was aimed to find out the effect of coping socialization towards the coping improvement in preventing stress on low economic society that is affected by COVID-19 in Bancah Lesung. This is quantitative research with a quasi-experiment. 144 samples were used chosen by a purposive sampling technique. This research was done in July 2020. The questionnaire is used as the instrument and the data were analyzed by univariate and bivariate analysis, the data then were tested by the Wilcoxon method. It is found that p-value = 0.000 which means that there are effects of coping promotion towards increased stress on low economic society in Bancah Lesung. It is recommended that the next researchers continue research regarding coping and include other variables such as using health education with video to improve coping.